PEMANFAATAN LIMBAH KATALIS RCC-15 PERTAMINA UP VI SEBAGAI GENTENG BETON - Kasam Kasam (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2005)
Waste management in particular catalyst waste of oil cracking industry has been many proposed by land disposal, but waste management by all at once reuse still be increased. This research are laboratory scale and application activity by make concrete roof-tile. The concrete roof-tile materials are used portland cement, fine coarse (sand), mill, and catalyst waste. The using of catalyst asadditif materials with compotition 0 %, 10%, 20 %, 30%, 40 %, 60 %, 80 %, and 50 %. The result of testing shown bending strength at 10 %, 20%, and 30% of catalyst waste are more than the normal concrete roof-tile ( 0% waste). That are 1,20, 12,33, and 11,00 kg/cm2 for10%, 20 %, 30%, % waste at the time that bending strength of normal concrete roof-tile is 10.97 kg/cm2. Testing of permebility shown that all of the sample are impermeable of water. The leaching experiment of heavy metal Cr, Pb, Zn, Ni and Cu on monolite matrix (concrete roof) by Toxicity Characteristic Leaching Procedure (TCLP) shows that the leaching of heavy metal is under standard. The greater leaching is Ni, that is 1,179 mg/L for 50% proportion of waste.